Child Distress Expression and Regulation Behaviors: A Systematic Review and Meta-Analysis - Hannah G. Gennis; Oana Bucsea; Shaylea D. Badovinac; Stefano Costa; C. Meghan McMurtry; David B. Flora; Rebecca Pillai Riddell (MDPI AG, 2022)
The goal of the current study was to review and meta-analyze the literature on relationships between child distress expression behaviors (e.g., cry) and three clusters of child distress regulation behaviors (disengagement of attention, parent-focused behaviors, and self-soothing) in the first three years of life. This review was registered with PROSPERO (CRD42020157505). Unique abstracts were identified through Medline, Embase, and PsycINFO (n = 13,239), and 295 studies were selected for full-text review. Studies were included if they provided data from infants or toddlers in a distress task, had distinct behavioral measures of distress expression and one of the three distress regulation clusters, and assessed the concurrent association between them. Thirty-one studies were included in the meta-analysis and rated on quality. Nine separate meta-analyses were conducted, stratified by child age (first, second, and third year) and regulation behavior clusters (disengagement of attention, parent-focused, and self-soothing). The weighted mean correlations for disengagement of attention behaviors were −0.28 (year 1), −0.44 (year 2), and −0.30 (year 3). For parent-focused behaviors, the weighted mean effects were 0.00 (year 1), 0.20 (year 2), and 0.11 (year 3). Finally, the weighted mean effects for self-soothing behaviors were −0.23 (year 1), 0.25 (year 2), and −0.10 (year 3). The second year of life showed the strongest relationships, although heterogeneity of effects was substantial across the analyses. Limitations include only analyzing concurrent relationships and lack of naturalistic distress paradigms in the literature.